Thematic Volume: Telecollaboration in Education for Foreign Language Teaching - ZAKIR, Maisa de Alcantara; FERREIRA, Michael J.; SOUZA, Micheli Gomes de; MESSIAS, Rozana Aparecida Lopes (The ESPecialist, 2022)
This thematic volume is an offshoot of the 1st GUTelOnX (Georgetown-UNESP Teletandem and Online Exchange Symposium)[1], an event held remotely on October 8th and 9th, 2020, based on a partnership between the research group “InViTe (Virtual Exchange and Teletandem): foreign languages for all[2],” from UNESP, and Georgetown University. The event brought together thirty-eight presentations by researchers and professors from universities and other types of educational contexts from around the world, to share their research and/or experiences in implementing telecollaborative language learning practices. This thematic issue brings together seventeen articles, which consist of works presented at the event and other studies from the academic community also focused on the role of technologies in foreign language teaching in promoting telecollaboration projects in several institutions around the globe. [1] http://telonx.georgetown.domains/ [2] InViTe (Virtual Exchange and Teletandem, in the acronym in Portuguese) is a continuation of “Teletandem Brazil: foreign languages for all” and gathers researchers from Brazil and other countries who implement and investigate the Teletandem context. http://dgp.cnpq.br/dgp/espelhogrupo/2209139477462677